NASKAH-NASKAH DI KERATON YOGYAKARTA: - Agus Iswanto (Jurnal Dialog, 2014)
This paper presents findings on the Javanese manuscripts available in Jogjakarta, particularly in the library of Jogjakarta Palace. The study portraits the relations between Islam and Javanese culture framed in these manuscripts. Some manuscripts contain the elements of normative Islam in its various genres, while some others are rich with the sincretic elements. These manuscripts elaborate the living Islam in the heart of the Javanese culture and society, especially in the Keraton context. From the historical point of views, this phenomenon is acceptable since along its process, Islam has always been through some interpretations, reinterpretations, and dialogues with and within the scope of cultures where Islam is spread.